Augmented reality and mixed reality behavior navigation system for telexistence remote assistance. (18th October 2021) - Oyama, Eimei; Tokoi, Kohei; Suzuki, Ryo; Nakamura, Sousuke; Shiroma, Naoji; Watanabe, Norifumi; Agah, Arvin; Okada, Hiroyuki; Omori, Takashi
Abstract : Considering the increased importance of telework systems in economies affected by COVID-19, telexistence technologies for remote guidance and navigation in general human activities are widely expected to prove beneficial in various applications, including plant maintenance, infrastructure inspection, and medical services. In prior work, we have proposed a behavior navigation system (BNS) using augmented reality (AR) and mixed reality (MR) technologies to provide remote assistance. Resembling a conventional gesture-based remote assistance system, our previously proposed motion guidance technology was designed to ensure that the motion of a non-expert user followed the motion of a remote expert sequentially and in a relatively accurate manner, similar to that of telexistence robots. As yet, the poor performance of head-mounted displays (HMDs) has presented major obstacles to the commercialization of BNSs. Enabled by the introduction of practical, modern HMDs, we present a novel BNS configuration and detail our implementation of the proposed system with an assessment of its performance. Experimental results show that compared to a conventional remote assistance system, our proposed approach achieved reduced working time, equal or increased task success rate (not statistically significant), and a higher subjective user evaluation. GRAPHICAL ABSTRACT: UF0001